STUDENTS’ WRITING HABITS OF ENGLISH STUDY PROGRAM AT FACULTY OF TEACHER TRAINING AND EDUCATION (FKIP) JAMBI UNIVERSITY - Fahmi, Alfin (Proceedings of English Linguistics and Literature, 2020)
The aim of this study was to investigate sixth-semester students’ writing habits of English study program. In this research, the researcher has researched about the writing type of the students based on the composing style, and also the researcher research the writing habits that sixth-semester students do in general. The data were collected by the closed-ended questionnaire and interview. This study involved 73 students of English study program from four classes Reguler (A and B) and Reguler Mandiri (H and I). The findings indicated that most of the students were heavy reviser. The total percentages of planner are 27 students (36.99%), reviser 38 students (52.05%), and sequential composer 8 students (10.96%). It also supported by the interview result to know about the students’ writing habits that they were difficult to determine the ideas of writing and the storyline. While students who have habit in writing they have the regular time to write every day. They usually use formal and informal writing. In the language use they usually use combination Indonesia and English language. Then, the influences of social media depend on their need. Furthermore, for the students who do not have habit in writing because they really did not like writing much, they do not have a lot of time, less of the idea in writing, and less of the vocabulary. Therefore, they answered it indicated that they had low interested.